Effectiveness and Predictors of Outcome for Psychotherapeutic Interventions in Clinical Settings Among Adolescents - Gergov, Vera; Lindberg, Nina; Lahti, Jari; Lipsanen, Jari; Marttunen, Mauri (Frontiers in Psychology, 2021)
Background: The aim of this study was to investigate the effectiveness of psychotherapeutic interventions for clinically referred adolescents, as well as to examine whether sociodemographic, clinical, or treatment-related variables and patients’ role expectations predict treatment outcome or are possible predictors of treatment dropout. Method: The study comprised 58 adolescents (mean age 14.2, 65.5% female) suffering from diverse psychiatric disorders referred to psychotherapeutic interventions conducted in outpatient care. The outcome measures, The Beck Depression Inventory, and the Clinical Outcomes in Routine Evaluation – Outcome Measure were filled in at baseline and at three-, six-, and 12-month follow-ups. Possible predictors were assessed at baseline. Results: The results indicate that the mean level of symptoms and psychological distress decreased during the treatment, most reduction occurring in the first six months. The frequency of treatment sessions was the strongest predictor of good outcome. Adolescents with a higher level of externalizing problems or lower level of expectations for their own active role in treatment seem to have a higher risk of dropping out. Conclusions: Offering intensive treatment for a shorter period might be the most efficient way to gain symptom reduction and decrease psychological distress in psychotherapeutic interventions with adolescents. Being aware of externalizing behavior and increasing the adolescents’ own agency during the assessment could strengthen commitment and result in the adolescent benefiting more from treatment.